2013
DOI: 10.1088/1742-6596/420/1/012110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental signals of a nuclear liquid-gas phase transition

Abstract: Zn at beam energy of 35 MeV/nucleon. Yields of fragments arising from fragmenting quasi-projectiles (QPs) with different neutron-proton asymmetries were analyzed within the framework of the Landau free energy approach. Fits to the free energy of fragments as a function of fragment asymmetry showed three minima, indicating the system to be in a regime of a first-order phase transition. The QP temperature estimates were extracted from the analysis of N=Z fragment data. Additionally, we make use of a recent metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These experimental quantities and the corresponding critical values have shown a dependence on the system neutron-proton asymmetry. This paper extends our previous analysis [32][33][34] using protons as probe particles. We now provide additional results from the same experimental data set by Coulomb correcting temperature and density values.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…These experimental quantities and the corresponding critical values have shown a dependence on the system neutron-proton asymmetry. This paper extends our previous analysis [32][33][34] using protons as probe particles. We now provide additional results from the same experimental data set by Coulomb correcting temperature and density values.…”
supporting
confidence: 80%
“…In our recent works [32][33][34], we have reported on the experimental temperatures and densities of fragmenting systems produced in near Fermi-energy heavy-ion collisions by means of a quantum fluctuation method for protons. Since the protons represent the vapor phase, the derived densities and temperatures were shown to sample the vapor branch of the liquid-gas coexistence curve.…”
mentioning
confidence: 99%
“…Several studies [24][25][26] have shown this energy domain to be the region of the nuclear liquid-gas phase transition. In our recent works [27][28][29][30][31][32], we have analyzed fragment yield data to investigate the nuclear phase transition using the Landau free-energy approach [33,34]. In such an approach, the key assumption is that in the vicinity of the critical point, the fragment free energy per nucleon (F ) relative to the system temperature (T ) can be expanded in a power series in the fragment's neutronproton asymmetry m as given by the relation…”
Section: Formalismmentioning
confidence: 99%
“…Previously [31,32,50] the data were sorted into four different QP asymmetry bins of width 0.05, ranging from 0.04 to 0.24. In a subsequent paper [51], it was shown that values of T and ρ that correspond to an asymmetry bin width close to zero (as it should be for fixed A and Z) could be obtained by averaging values for all four asymmetry bins.…”
Section: Temperature and Densitymentioning
confidence: 99%
See 1 more Smart Citation